Saobraćajna situacija SR Hrvatske s aspekta turističke potražnje - TOMIĆ, Ivica (Promet - Traffic&Transportation, 2026)
SITUATION IN TRAFFIC IN THE SR OF CROATIA FROM THE ASPECT OF TOURIST SERVICES DEMAND This paper deals with traffic situation in the SR of Croatia providing a review of its impacts on the development of tourist industry and respective problems as manifested in traffic i.e. transport, all in order to help the latter reinvigorate the tourist industry activities. Particular accent is assigned to the development of set transport and in this respect the paper discusses the developing plans for both sea and other aspects of transport of particuh seaside orientation.